2011
DOI: 10.3846/bme.2011.01
|View full text |Cite
|
Sign up to set email alerts
|

Material Flow Cost Accounting (Mfca) – Tool for the Optimization of Corporate Production Processes

Abstract: The paper focuses on the Material Flow Cost Accounting method (hereinafter the “MFCA”). It presents an application of the MFCA within a manufacturing plant of the largest manufacturer of ceramic tiles in the Czech Republic – the company Lasselsberger. It shows the importance of data acquired from the MFCA system as well as their application for an optimization of manufacturing processes for specific conditions of a manufacturing plant of the company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 3 publications
0
16
0
5
Order By: Relevance
“…MFCA is a key tool of management approach known as flow management that aims specifically to manage manufacturing processes related to material flow, energy, and data so that the manufacturing process can be more efficient and in accordance with the targets set (Hyrslova et al 2011;Viere et al 2011). MFCA is a management information system that explores all input materials that flow in the production process and measures the output in the finished product and waste (Kokubu and Kitada, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFCA is a key tool of management approach known as flow management that aims specifically to manage manufacturing processes related to material flow, energy, and data so that the manufacturing process can be more efficient and in accordance with the targets set (Hyrslova et al 2011;Viere et al 2011). MFCA is a management information system that explores all input materials that flow in the production process and measures the output in the finished product and waste (Kokubu and Kitada, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this accounting, costs and material losses of energy are usually not counted, and because the material cost can be directly allocated to production cost, the cost will instantly cut the cost center in the cost of goods sold of the company so that the company management will immediately focus on reducing it. Furthermore, Hyrslova et al (2011), Viere et al (2011) and Ichimura (2012), categorize MFCA as a management tool showing the flow of materials with a focus on the importance of information to optimize the production process. The aims are to present the system at the output of finished goods and demonstrate the importance of the data obtained from the MFCA system for optimization of manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…MFCA analysis captures costs of physical and monetary information of material and monetary flows in a process and separates process output into good or negative product to reveal inefficiencies in the process (Hargroves and Smith 2012). The MFCA model analyses material flow, energy and operation costs of production into product and non-product or waste output (Jasch 2009;Kokubu et al 2009;Hyršlová et al 2011).…”
Section: Materials Flow Cost Accountingmentioning
confidence: 99%
“…But studies have shown that the adoption of MFCA is more relevant in providing both financial and non-financial waste information necessary for improved waste-reduction decisions (Wagner 2003a;METI 2007;Jasch 2009). Although there has been a substantial amount of study on the adoption of MFCA to improve wastereduction decisions within organizations, especially in Europe and Asia (METI 2007;Jasch 2009;Kokubu et al 2009;Debnath 2014), the majority of these studies has focused on large-and medium-sized organizations (METI 2007;Jasch 2009;Kokubu et al 2009;Onishi et al 2009;Hyršlová et al 2011). Consequently, this study reports findings from a pilot study conducted in a micro-brewery that demonstrate the adoption of the MFCA model to capture adequate waste-cost information to support and improve waste-reduction decisions.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, these environmental costs are often obscured into general overhead costs in traditional accounting systems, rendering managers to incapable observing them (Ferreira et al 2010). To address this problem, the material flow cost accounting (MFCA) system was developed to provide advanced cost analysis by identifying, classifying, and allocating these costs to reduce the level of negative products, which effectively reduced the costs by 5% or more (Hyrslova et al 2008). MFCA is a basic tool of Environmental Management Accounting (EMA) (Kokubu & Tachikawa 2013).…”
Section: Introductionmentioning
confidence: 99%